Transcriptomic and Epigenomic Dynamics of Honey Bees in Response to Lethal Viral Infection - Li-Byarlay, Hongmei; Boncristiani, Humberto; Howell, Gary; Herman, Jake; Clark, Lindsay; Strand, Micheline K.; Tarpy, David; Rueppell, Olav (Frontiers in Genetics, 2020)
Honey bees (Apis mellifera L) suffer from many brood pathogens, including viruses. Despite considerable research, the molecular responses and dynamics of honey bee pupae to viral pathogens remain poorly understood. Israeli Acute Paralysis Virus (IAPV) is emerging as a model virus since its association with severe colony losses. Using worker pupae, we studied the transcriptomic and methylomic consequences of IAPV infection over three distinct time points after inoculation. Contrasts of gene expression and 5mC DNA methylation profiles between IAPV-infected and control individuals at these time points—corresponding to the pre-replicative (5 hr), replicative (20 hr), and terminal (48 hr) phase of infection—indicate that profound immune responses and distinct manipulation of host molecular processes accompany the lethal progression of this virus. We identify the temporal dynamics of the transcriptomic response to with more genes differentially expressed in the replicative and terminal phases than in the pre-replicative phase. However, the number of differentially methylated regions decreased dramatically from the pre-replicative to the replicative and terminal phase. Several cellular pathways experienced hyper- and hypo-methylation in the pre-replicative phase and later dramatically increased in gene expression at the terminal phase, including the MAPK, Jak-STAT, Hippo, mTOR, TGF-beta signaling pathways, ubiquitin mediated proteolysis, and spliceosome. These affected biological functions suggest that adaptive host responses to combat the virus are mixed with viral manipulations of the host to increase its own reproduction, all of which are involved in anti-viral immune response, cell growth, and proliferation. Comparative genomic analyses with other studies of viral infections of honey bees and fruit flies indicated that similar immune pathways are shared. Our results further suggest that dynamic DNA methylation responds to viral infections quickly, regulating subsequent gene activities. Our study provides new insights of molecular mechanisms involved in epigenetic that can serve as foundation for the long-term goal to develop anti-viral strategies for honey bees, the most important commercial pollinator.